2013
DOI: 10.1002/eat.22083
|View full text |Cite
|
Sign up to set email alerts
|

White matter integrity is reduced in bulimia nervosa

Abstract: Objective To investigate brain white matter (WM) functionality in bulimia nervosa (BN) in relation to anxiety. Method Twenty-one control (CW, mean age 27±7 years) and 20 BN women (mean age 25±5 years) underwent brain diffusion tensor imaging (DTI) to measure fractional anisotropy (FA; an indication of WM axon integrity) and the apparent diffusion coefficient (ADC; reflecting WM cell damage). Results FA was decreased in BN in the bilateral corona radiata extending into the posterior limb of the internal cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 74 publications
9
43
0
Order By: Relevance
“…Our data complement and expand previous findings from other groups that utilized dMRI to show an inverse relationship between frontotemporal white matter strength and trait anxiety/anxiety-related constructs (e.g., harm avoidance, neuroticism) in nonclinical populations (Kazlouski et al, 2011; Motzkin et al, 2011; Westlye et al, 2011; Taddei et al, 2012; Bjørnebekk et al, 2013; Mettler et al, 2013; Eden et al, 2015; Greening and Mitchell, 2015). Collectively, these findings support the notion that stronger connectivity between the amygdala and the vPFC reflects the capacity for efficient crosstalk between these brain regions that ultimately leads to beneficial outcomes in terms of anxiety (Kim et al, 2011b).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our data complement and expand previous findings from other groups that utilized dMRI to show an inverse relationship between frontotemporal white matter strength and trait anxiety/anxiety-related constructs (e.g., harm avoidance, neuroticism) in nonclinical populations (Kazlouski et al, 2011; Motzkin et al, 2011; Westlye et al, 2011; Taddei et al, 2012; Bjørnebekk et al, 2013; Mettler et al, 2013; Eden et al, 2015; Greening and Mitchell, 2015). Collectively, these findings support the notion that stronger connectivity between the amygdala and the vPFC reflects the capacity for efficient crosstalk between these brain regions that ultimately leads to beneficial outcomes in terms of anxiety (Kim et al, 2011b).…”
Section: Discussionsupporting
confidence: 87%
“…The current data are consistent with a recent finding that highlights a female-specific inverse relationship between amygdala-vPFC resting state functional connectivity and self-reported anxiety symptoms (Burghy et al, 2012). Further, a number of previous studies showing an inverse relationship between the structural integrity of an amygdala-vPFC pathway and trait anxiety consisted of dMRI data derived entirely from females (Kazlouski et al, 2011; Mettler et al, 2013; Eden et al, 2015). Finally, an additional study showed a female-specific positive correlation between the structural integrity of the uncinate fasciculus and self-reported use of reappraisal strategy during emotion regulation (Zuurbier et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…62 These mixed results might reflect the effects of overlapping pathophysiological mechanisms in the fornix. It is also interesting to note that these mechanisms might be nonspecific to patients with anorexia nervosa, restricting subtype, since a similar pattern of microstructural alterations in the fornix has been found in patients with bulimia nervosa 63 and in overweight and obese individuals. 64 Even if some of these conditions have opposite behavioural consequences, some shared biological effects are suggested, 65 and it is likely that extreme weight conditions might have similar structural effects in this energy balance system.…”
Section: Changes In the Fornixmentioning
confidence: 88%
“…When measured with structural MRI, BN participants were characterized by increased gray matter volumes within the ventral anterior insula (Frank et al, 2013) and when measured by DTI, BN participants displayed disturbed white matter integrity within the right sub-insula (Mettler et al, 2013). …”
Section: Resultsmentioning
confidence: 99%